Towards a strategy for pro-poor growth in South-Eastern Europe - Hermann Sautter (Georg-August-Universität Göttingen, Ibero-America Institute for Economic Research (IAI), 2005)
In order to qualify economic growth as 'pro-poor', at least per capita income-growth rates of the poor should be larger than the corresponding growth-rates of the non-poor resulting in a lower degree of distributional inequality. Measured in this sense, economic growth in South- Eastern Europe during the last 10-15 years was not pro-poor but pro-rich. Future growth can be changed towards the 'pro-poor'-goal through a strategy with two 'legs': Stimulation of overall growth and specific programs to make economic growth 'pro-poor'. Overall growth can be stimulated by good governance, macro-economic stability and the establishment of competitive markets. Specific programs should be focussed on sectors the poor work in (mainly agriculture), on regions the poor live in (mainly rural areas) and on the demand for factors the poor possess or are able to possess (labour). The paper discusses some elements of rural development, the possibilities of stimulating the demand for labour, and the necessary steps to improve the access of the poor to education and health-services. In addition to that, the problems of 'pockets of poverty' are being discussed. A consistent strategy like this requires political decisiveness and administrative competence. It is hard to imagine that it can be materialized without giving the poor 'voice' to influence the institutions and policies that affect their lives.
Keywords: 330